Ancient psychoactive drugs in Ecuador:: between symbolic struggles and cultural appropriation - Burgaleta, Elena (2023)
This article is focuses the issue of cultivation and use of psychoactive drugs in the context of indigenous communities in Ecuador. In this regard, it proposes to analyze, from the perspective of social fields and symbolic struggles, how psychoactive drugs are an efficient capital for the State and the market, specifically for the psychedelic tourism industry. The redefinition of this cultural heritage as a consumer product and its progressive adjustment to postmodernisms linked to mystical practices, translates into a cultural appropriation of sacred elements and practices. The media portrays two opposing scenarios: the State with a punitive and prohibitionist discourse, and the indigenous peoples and nationalities defending the sacred nature and therapeutic properties of these substances. Methodologically, the following concepts headed in this research are national and international drug policies based on information gathered from previous studies, regulations, academic and institutional discourses, aiming to generate a critical reflection that allows for new proposals on the regulation and cultural protection of the use and consumption of ancestral psychoactive drugs in Ecuador.